Optimization of a reinforced concrete structure subjected to dynamic wind action (Fracture and Structural Integrity, 2021)
This work proposes a methodology to optimize a reinforcedconcrete structure. For this, the Whale Optimization Algorithm (WOA)algorithm was used, an algorithm from the group of metaheuristicalgorithms, which presents an easy computational implementation. As astudy object, a frame structure adapted from a real reinforced concretebuilding was used, subjected to the dynamic action of artificially generatedsynoptic wind. The objective function is to reduce the volume of concreteof the structure. For that, the dimensions of the cross-sections were used asdesign variables, and the maximum displacement at the top imposed by theASCE / SEI 7-10 standard as a lateral constraint, as well as the maximumstory drift between floors. In addition to this structural optimization, it wasalso proposed the use and optimization of Tuned Mass Dampers (TMD), indifferent quantities, positions and parameters, improving the dynamicresponse of the reinforced concrete building. The results show that for thissituation it was possible to reduce the concrete volume of the structure byapproximately 24%, respecting the maximum limit of displacement at thetop required by the standard.
Keywords: optimization; concrete structure; metaheuristic algorithms